Local sourcing and the military: Lessons learned through a university-based initiative to increase local procurement at a US military base. Issue 3 (18th September 2017) - Dunning, Rebecca; Day, John; Creamer, Nancy
Abstract: The volume of food purchased by the American military makes it perhaps the single largest intermediated market for food in the USA. Consequently, it is not surprising that those seeking to enhance the economic viability of small and mid-scale farms may view military bases as a promising market for locally produced foods. This is a challenging prospect, however, due to the centralized structure of military command, the nature of the military procurement system and federal mandates to obtain products that maximize value at the lowest available cost. This paper describes the US military food procurement system and the work of a 3-yr initiative to increase the amount of locally produced, source-identified products used at a North Carolina military installation. Our experiences serve as a cautionary tale, with this paper designed as both a primer on 'how it works' for food procurement at the federal and base level, and a description of our largely unsuccessful attempts to increase the volume of local food products from small-/mid-scale producers moving through the supply chain into base dining halls and restaurants. Based on our experiences, we also make recommendations on possible entry points for local food and farm advocates to work within the existing system to localize food procurement.